HUBUNGAN POLA ASUH OTORITER ORANG TUADENGAN MINAT BELAJAR SISWA KELAS VIII MTs. DARUL ILMI TAHUN AJARAN 2021/2022 - Dinda Aulia Putri (PUSKAPAD, 2025)
Parents have a responsibility towards their children in terms of education. Parental attention both in terms of moral and material is one of the factors that foster children's enthusiasm for learning. This study aims to determine the relationship between authoritarian parenting styles and the learning interests of class VIII students of MTs. Darul Ilmi in the 2021-2022 academic year. The method in this study is quantitative with a correlation approach. The population in this study were 118 class VIII students of MTs. Darul Ilmi in the 2021-2022 academic year, and the sampling technique in this study was the Purposive sampling technique. Researchers use this technique because researchers want to determine students who get authoritarian parenting from their parents. Researchers can determine samples that get authoritarian parenting from their parents by distributing a valid authoritarian parenting questionnaire, if the score results from the distribution of the questionnaire are high then the students are made a sample of 65 students. The data collection instrument used in this study is a questionnaire. The questionnaire has been tested for validity and reliability, namely with the results of 36 valid questionnaire items on the authoritarian parenting questionnaire and 35 valid questionnaire items on the learning interest questionnaire. The correlation test technique uses the product moment correlation formula, from the calculation results obtained a correlation coefficient between authoritarian parenting (X) and learning interest (Y) of r count = 0.721> r table = 0.250. In accordance with the interpretation of the product moment correlation index, the number indicates a relationship between the two variables. The results of this test state that there is a significant relationship between authoritarian parenting and learning interest in Grade VIII MTs students. Darul Ilmi Academic Year 2021-2022.